Algae as an emerging source of bioactive pigments. (May 2022) - Patel, Anil Kumar; Albarico, Frank Paolo Jay B.; Perumal, Pitchurajan Krishna; Vadrale, Akash Pralhad; Nian, Cherry T; Chau, Ho Thi Bao; Anwar, Choirul; Wani, Henna Mohi ud din; Pal, Anugunj; Saini, Reetu; Ha, Le Hai; Senthilkumar, Balamurugan; et al.
Graphical abstract: Highlights: Algae are emerging as a major source of safe bioactive pigments. Algal pigments offer 2–10 folds higher bioactivity than synthetic pigments. Algal pigments find application in pharma-, cosma- and nutraceuticals etc. Their demands are rising due to increased bioactivity and no side effects. Algal pigment market value is expected to reach 452.4 million USD by 2025. Abstract: Algae have been identified as natural producer of bioactive commercial pigments. To perform photosynthesis, algae use pigments to harvest sunlight energy. The pigments found in algae are categorized in chlorophylls, phycobilins, and carotenoids. Popular carotenoids include astaxanthin, lutein,  fucoxanthin, canthaxanthin, zeaxanthin, β-cryptoxanthin and finds application as antioxidant, anti-inflammatory, immunoprophylactic, antitumor activities among others. Due to double-bonds in their structure, they exhibit broad health applications while protecting other molecules from oxidative stress induced by active radicals using various mechanisms. These carotenoids are synthesized by certain species as major products however they also present as byproducts in several species based on the pathway and genetic capability. Haematococcus pluvialis and Chlorella zofingiensis are ideal strains for commercial astaxanthin production. This review provides recent updates on microalgal pigment production, extraction, and purification processes to standardize and analyze for commercial production. Also, discussed the factors affecting its production, application, market potential, bottlenecks, and future prospects.